2021
DOI: 10.1111/1759-7714.13902
|View full text |Cite
|
Sign up to set email alerts
|

Third‐generation EGFR inhibitor HS‐10296 in combination with famitinib, a multi‐targeted tyrosine kinase inhibitor, exerts synergistic antitumor effects through enhanced inhibition of downstream signaling in EGFR‐mutant non‐small cell lung cancer cells

Abstract: Background As a highly heterogeneous disease, lung cancer has a multitude of cellular components and patterns of gene expression which are not dependent on a single mutation or signaling pathway. Thus, using combined drugs to treat lung cancer may be a practical strategy. Methods The combined antitumor effects of HS‐10296, a third‐generation EGFR inhibitor targeting EGFR T790M mutation, with the multitargeted tyrosine kinase inhibitor (TKI) famitinib in non‐small cell lung cancer (NSCLC) were evaluated by in v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 23 publications
2
10
0
Order By: Relevance
“…Single doses of famitinib 25mg were well tolerated in healthy subjects when given alone and in combination with multiple doses of rifampin. The major adverse reactions (incidence rate >30%) after continuous administration of famitinib in cancer patients were hypertension, hand-food skin reaction, oral mucositis, bone marrow suppression, diarrhea, proteinuria, hypertriglyceridemia, fatigue, liver dysfunction, etc [3,5,6,8]. In this study, the famitinib-related adverse events were in line with the known safety profile.…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…Single doses of famitinib 25mg were well tolerated in healthy subjects when given alone and in combination with multiple doses of rifampin. The major adverse reactions (incidence rate >30%) after continuous administration of famitinib in cancer patients were hypertension, hand-food skin reaction, oral mucositis, bone marrow suppression, diarrhea, proteinuria, hypertriglyceridemia, fatigue, liver dysfunction, etc [3,5,6,8]. In this study, the famitinib-related adverse events were in line with the known safety profile.…”
Section: Discussionsupporting
confidence: 79%
“…famitinib, SHR1020), is an orally active, small-molecule, multi-targeted and potent TKI that inhabits various TKRs including c-Kit, platelet-derived growth factor receptor (PDGFR), vascular endothelial growth factor receptor (VEGFR), FMS-like tyrosine kinase-3 receptor (FLT3), KDR and RET. Famitinib not only inhabits the angiogenesis, but also directly inhabits the expansion of tumor cells, which have been verified both in vivo and in vitro [2,3]. Completed Phase I and II studies in patients with advanced solid cancer have demonstrated that famitinib is well tolerated and has a broad spectrum of antitumor activities [4][5][6][7][8].…”
Section: Introductionmentioning
confidence: 89%
“…famitinib, SHR1020) is an orally active, small-molecule, multi-targeted and potent TKI that inhibits various TKRs including c-Kit, platelet-derived growth factor receptor (PDGFR), vascular endothelial growth factor receptor (VEGFR), FMS-like tyrosine kinase-3 receptor (FLT3) and RE arranged during Transfection (RET). Famitinib not only inhibits the angiogenesis, but also directly inhibits the expansion of tumor cells, which have been verified both in vivo and in vitro [ 2 , 3 ]. Completed Phase I and II studies in patients with advanced solid cancer have demonstrated that famitinib is well tolerated and has a broad spectrum of antitumor activities [ 4 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…Famitinib is a structural analog of sunitinib with improved cell inhibitory activity. Due to its anti-angiogenic effect, it was effective against metastatic renal cell carcinoma, non-small cell lung cancer and metastatic breast cancer [11][12][13] . Clinical trials of famitinib in combination with the concurrent medication or chemoradiotherapy also showed its good antitumor abilities against other solid tumors such as metastatic urothelial carcinoma, advanced immunomodulatory triple-negative breast cancer, advanced nasopharyngeal carcinoma, platinum-resistant recurrent ovarian cancer, advanced colorectal cancer and gastric cancer 9,[14][15][16][17][18][19][20] .…”
Section: Introductionmentioning
confidence: 99%